Graphene and polarisable nanoparticles: Looking good together? - Vasilevskiy, Mikhail (2016)
Several potentially interesting plasmonic effects can arise from combining graphene with polarisable nanoparticles (NPs), such as metallic or dielectric spheres, related to surface plasmon-polaritons (SPPs) supported by the latter in the terahertz (THz) spectral range. Owing to the electromagnetic coupling between the graphene SPPs and dipole moments of polarisable (nano-) particles deposited on top of it, the optical properties of such a composite system have some new features as compared to its constituents. First, the NP’s polarisability is renormalised due to the electromagnetic back action of SPPs which are excited in graphene when an external propagating electromagnetic wave impinges on the particle. The coupling also results in a considerable enhancement of the THz radiation absorption in graphene, while the reflection drops to zero. This effect can be potentially interesting e.g. for cloaking in a certain THz frequency range.